ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP MINAT BELI KONSUMEN PRODUK BATIK SENDANG DUWUR LAMONGAN - MARTONO R A P, M (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: Batik is an original Indonesian cultural heritage in Indonesia there are several areas one of which is a producer of batik village Sendang Duwur Lamongan. Competition batik products are increasingly stringent demands batik producers to better maintain the Sendang Duwur quality price and promotional products to batik Sendang Duwur able to compete with batik from other regions.this study was conductedwitha questionnaireon thespreadof civil servantsand privateinLamongandistrictas therespondent data. Probability samplingtechniquesamplingwithsimple random sampling, methodsof analysis usedin this studyis theMultiple Linear Regression, processingof datausingSPSSstatisticalprogram. The results showedthat there wasa significant effectofthe variablepriceproduct qualityandpromotion ofconsumerinterest in buyingbatikSendangDuwurLamongan. The promotionisthe mostdominantvariablewith a valueoft count. Keywords:quality ofproduct, price, promotion, and buyinterests.